Subclinical mastitis in a pampinta dairy sheep flock in the la pampa province (Semiárida, 2021)
Some aspects of the Pampinta sheep, a synthetic breed developed in the EEA of Anguil, constituted by East Friesian (East Friesian) and Corriedale, have been studied. Considered as triple purpose (meat, milk and wool), but phenotypically selected towards the East Friesian breed, being one of the main breeds that is used in milking in Argentina. The objective of this work is to describe the subclinical mastitis (MSC) that occur in the flock of the Tambo Model of the Experimental of Anguil, with data collected in the dairy controls between 2009 and 2014. An animal model was a used with random effects and fixed effects such as age at childbirth; year of lactation; type of breeding and parturition and milk production class. The SAS statistical program was used for the production data and a Threshold Model (TM, Legarra et al., 2008) for mastitis. The graphics were made through the Infostat R package (R Core Team, 2013). Milk production was not related to the incidence of mastitis. The somatic cell count (SCC) varies throughout lactation, having high values at the beginning, then decreases and remains. The age, the presence of MSC and the level of milk production are factors that influence the SCC. The environment where animals are found can have stressors that can interfere with the immune system. More studies are needed and in order establishments in order to generalize results, which must be taken into account that there is a demand in the selection processes.
Keywords: Pampinta; sheep; subclinical mastitis; milk production; somatic cell count;